Adiponectin enhances Imatinib anti‐tumour activity in human chronic myeloid leukaemia cells with serum levels associated with Imatinib efficacy in early chronic phase patients. (August 2015) - Tan, Guangshan; Shi, Lei; Li, Qiang; Wang, Mingjun
Abstract Objectives Adiponectin, a functional ligand of adiponectin receptor‐1 (AdipoR1) and adiponectin receptor‐2 (AdipoR2), has been found to be linked to risk of development of chronic myeloid leukaemia (CML). Imatinib, as its first‐line therapy, exhibits striking activity in both chronic and accelerated phases of the condition. However, numerous clinical trials have shown that many patients become refractory or experience relapses. Thus, development of new, hopefully effective Imatinib‐based treatment strategies, are still needed. Materials and methods Effects of recombinant adiponectin protein, in enhancing Imatinib anti‐tumour activities, in K562 and MEG‐01 CML cells, were examined in vitro and in vivo. Forty‐eight consecutive newly diagnosed adult patients with Bcr‐Abl‐positive CML, in the early chronic phase (ECP), were enrolled in the study. Imatinib efficacy, plasma adiponectin levels and their correlations were analysed. Results Data presented here indicate that adiponectin enhanced Imatinib efficacy in vitro and in vivo. Furthermore, this augmented effect was due to inhibition of Bcr‐Abl tyrosine kinase activity in an AdipoR1‐dependent way, while AdipoR2 was not involved. Most importantly, additional clinical data revealed that adiponectin plasma levels in CML ECP patients, correlated with Imatinib efficacy. Conclusions Adiponectin enhanced Imatinib anti‐tumour activity in human chronic myeloid leukaemia cells and its serum levels were associated with Imatinib efficacy, in early chronic phase patients.